Effect of Medium Instruction on Academic Performance of The Students at Secondary Schools in Hargeisa Somaliland - Ahmed Gahayr Abdullahi (Tinta Emas Publisher, 2024)
The study investigated the effect of medium of instruction on performance of students in secondary schools in Hargeisa district in Somaliland. The study arose from the fact that the quality of education in Somaliland had dropped and this had been blamed on medium of instruction among other factors. The study specifically investigated the effect of medium of instruction on knowledge acquisition, on skill acquisition and attitude development by students in secondary schools in Hargeisa District. Data was collected from 342 students of form two classes in Secondary schools in Hargeisa using questionnaire and analyzed by t-test analysis method. The study found that medium of instruction does not affect the knowledge acquisition of the student, t (250) = 1.618, p = .107. But medium of instruction affects the skill acquisition of the students, t (250) = 3.977, p = .000, and attitude development of the students, t (250) = 2.047, p = .042. The study concludes that medium of instruction affects the performance of the students in secondary school in Hargeisa district.